Hydrological Behavior of an Infiltration-Induced Landslide in Colorado, USA. (3rd June 2019) - Wayllace, Alexandra; Thunder, Barbara; Lu, Ning; Khan, Aziz; Godt, Jonathan W.
Abstract : Infiltration-induced landslides are common in mountainous and hilly areas of the world. When they occur near transportation corridors, they can impact public safety, impede transport of goods and people, and damage transportation infrastructure. This work presents a study of the hydrological behavior and its effects on the stability of an active landslide located on an embankment along Interstate-70 west of the Eisenhower Tunnel in central Colorado, USA. Groundwater dynamics were monitored for three years; two piezometers were installed near the head of the slide and one piezometer was placed near the toe. The hydrological observations at this site are unusual in that water table positions beneath the westbound shoulder of the highway (upslope) varied twice as much as water table positions beneath the eastbound shoulder (downslope), only 30 m distant horizontally. To better understand the factors controlling these observed differences, observations of the stratigraphy and the geomorphology of the watershed beyond the landslide body were incorporated into a conceptual model tested using numerical simulations of two-dimensional, variably saturated groundwater flow. Results from the numerical simulations calibrated against field measurements and a seasonally varying stability analysis of the site show that the large observed differences in the water table positions over the short horizontal distance are likely due to a combination of (1) the large size of the watershed that allows a significant amount of infiltration of snowmelt into the hillslope, (2) the contrast of hydrological properties of soils in the watershed, and (3) the changes in steepness of the dip of the bedrock below the slide. These three factors control the direction, speed, and amount of groundwater flow traveling through the slope. It is also shown that the seasonal hydrology of the site is a key factor in the stability of the slope, where most of the observed displacement occurs during the early summer season. Variations in the water table level within a year resulting from low snow years compared to variations from high snow years can be as much as 100%. Finally, it is important to consider the large contributing area of the watershed when evaluating the hillslope hydrologic conditions and remediation options.